알칼리 처리된 떫은감 추출물의 산화방지능 및 PC-12 신경세포 모델에서의 보호 효과 - 이현복; 정하람; 황교하; 이승환; 김태완; 김석진; 김대옥 (한국식품과학회지, 57(2), 2025)
Immature astringent persimmon (IAP) contains high levels of tannins, which affect the gel formation of the IAP extract (IAPE), limiting its food applications. In this study, the IAPE was derived from a by-product of persimmon fruit thinning in Diospyros kaki Thunb. cv. Cheongdo-Bansi. Alkali and heat treatments were applied to prevent gelation of the IAPE. The total phenolic and flavonoid contents, antioxidant capacity, and gallic acid content of heat-treated IAPE (HIAPE) and alkali-treated IAPE (AIAPE) were measured, along with the neuroprotective effects and cholinesterase inhibitory activity of AIAPE. While the total phenolic and flavonoid contents showed no significant differences between AIAPE and HIAPE, AIAPE exhibited significantly (p<0.05) higher antioxidant capacity and gallic acid content compared to HIAPE. Additionally, AIAPE enhanced the viability of PC-12 cells by reducing H2O2-induced intracellular oxidative stress and dose-dependently inhibited both acetylcholinesterase and butyrylcholinesterase. These findings suggest that AIAPE has potential as a functional food ingredient. KCI Citation Count: 0